Bridging the Intention–Behavior Gap in Green Consumption: An Integrated Framework of Sustainable Repurchase Behavior - Hermawan, Muhammad Distian Andi (Entrepreneurship and Small Business Research, 2024)
Recent advances in green consumer research have increasingly emphasized sustainable repurchase behavior as a critical indicator of long-term environmental commitment and business sustainability. However, existing studies remain theoretically fragmented, employing diverse models and constructs without a unified framework to explain how determinants, mediators, and moderators interact in shaping green repurchase intentions. This study develops an integrated conceptual framework of sustainable repurchase behavior through a Systematic Literature Review (SLR) guided by PRISMA 2020. Drawing on 72 peer-reviewed articles published between 2018 and 2025 from Scopus, ScienceDirect, and Google Scholar, the analysis systematically maps key determinants, mediators, and moderators within green consumer research. The findings reveal that Green Perceived Value (GPV) consistently emerges as the most dominant determinant of green repurchase intention. Its influence operates both directly and indirectly through critical mediators, particularly green trust, green satisfaction, and attitudes toward green products. Furthermore, contextual moderators such as green knowledge, green social media engagement, and regulatory environments significantly shape the strength of these relationships. The study demonstrates that sustainable repurchase behavior is not a linear outcome of intention but the result of complex, multi-layered psychological and contextual interactions. This research contributes by proposing a unified, integrative framework that consolidates TPB, VAB, and ECT perspectives, offering clearer theoretical coherence and practical guidance for advancing sustainable consumption strategies.